Le patrimoine photographique malien et ses enjeux - Érika Nimis (Continents manuscrits)
For some fifteen years, Mali and more specifically Bamako, its capital city, host to an international photography festival since 1994, have been acting as a ‘laboratory’ for several projects showcasing Africa’s photographic heritage. This article addresses the more recent projects, initiated, in whole or in part, by Malian players, while pointing out that these projects follow in the footsteps of the recognition of the works of Bamako studio photographers Seydou Keita and Malick Sidibé, initially supported by the Western art market. This article thus attempts to trace the main outline of this movement for recognition which, having its starting point in initiatives coming from outside in the 1990s, gradually led the political and cultural authorities of Mali to consider the heritage value of the photographic archives preserved in the country, as part of a democratic revival.